Deep-sea ascidians from Papua New Guinea - Monniot, Françoise; López-Legentil, Susanna (Zootaxa, 2017)
Four deep-sea ascidian species collected during the KAVIENG 2014 expedition in Papua New Guinea are described, including additional characteristics not reported previously. Fimbrora calsubia is classified within the family Ascidiidae, Dicopia fimbriata and Octacnemus bythius within Octacnemidae, and Culeolus recumbens within Pyuridae. Anatomical observations confirmed previous descriptions for these four species collected elsewhere. Here, we describe additional morphological features for these species and provide the first barcode DNA sequences (based on a fragment of the mitochondrial gene Cytochrome Oxidase I) for D. fimbriata and C. recumbens.